(untitled) (Ustozlar uchun, 2026)
This article analyzes the poetics of unconventional imagery in Uzbek literature using the example of the story "In the Wing of a Swan" by the famous writer Shodikul Hamro. Innovations in Uzbek literature are based on various principles, and in particular, it is impossible not to emphasize the influence of masterpieces of world literature. This influence should not be overlooked in the manifestation of unconventional imagery in the story analyzed above by Shodikul Hamro. The writer tries to artistically express the idea he put forward in his story: that a person lives without forgetting himself, his roots, origin, spiritual and spiritual integrity, through unconventional imagery. In this, the writer brings every detail to its place and further enriches the plot through the nature of landscape, portrait, lyrical experience and monologue speech.